The learning impact of the Online Formative Assessment system (OFAs) for undergraduate medical students - Sari, Sylvia M; Saadah, Hindun (ACTA Medical Health Sciences, 2022)
Formative assessment is a continuum process of evaluating students’ performance to enhance students’ learning quality. The shift to full-online learning in pandemics reduces student-lecturer attachments during formative assessment. Therefore, we developed the Online Formative Assessment system (OFAs) based on a self-regulatory learning framework. This study aimed to explore the learning impact of OFAs, such as learning preparation, feedback perception, and self-reflection. We used the mixed method with an exploratory approach. We collected quantitative data from 150 students who experienced OFAs, using 26 questions adapted from AEQ (Assessment Experience Questionnaire) and analyzed by pre-post design (paired-T test). To explore a deeper understanding, we conducted 6 FGDs (N=28). Finally, we analyzed the quantitative and qualitative data sequentially. We found the difference in students’ preparation (p<0.5), feedback perception (p<0.5), and no difference in self-reflection (p>0.5). In Qualitative data, we found three themes as follows: (1) OFAs improve student preparation in learning; 2) Students are aware of being assessed during tutorials; 3) Require more specific and individual written feedback; 4) Lack of self-reflection due to unspecific feedback. These findings represent that learning impact is a complex pathway that online assessment systems can drive. It needs externally driven feedback quality and internally driven factors such as self- reflection skills. However, we found the challenges to improving students' quality feedback and self-reflection skills. This study brings further research on student-lecturer engagement in online formative assessment. DOI : 10.35990/amhs.v1n2.p71-78 REFERENCES Preston, R., Gratani, M., Owens, K., Roche, P., Zimanyi, M., & Aduli, B. M. (2020). Exploring the impact of assessment on medical students’ learning. Assessment & Evaluation in Higher Education, 45(1), 109–124. Norcini, J., Anderson, M. B., Bollela, V., et al. (2018). Consensus framework for good assessment. Medical Teacher, 2. https://doi.org/10.1080/0142159X.2018.1500016 Kulasegaram, K., & Rangachari, P. K. (2018). Beyond “formative” assessments to enrich student learning. Advances in Physiology Education, 42(1), 5–14. https://doi.org/10.1152/advan.00122.2017 Wiliam, D. (2011). What is assessment for learning?. Studies in Educational Evaluation, 37, 3–14. https://doi.org/10.1016/j.stueduc.2011.03.001 Schuwirth, L. W. T., & Van der Vleuten, C. P. M. (2011). Programmatic assessment: From assessment of learning to assessment for learning. Medical Teacher, 33, 478–485. Larsen, D. P., Butler, A. W., & Roediger, H. L. (2008). Test-enhanced learning in medical education. Medical Education, 42, 959–966. https://doi.org/10.1111/j.1365-2923.2008.03124.x Green, M. L., Moeller, J. J., & Spak, J. M. (2018). Test-enhanced learning in health professions education: A systematic review (BEME Guide No. 48). Medical Teacher, 40(4), 337–350. https://doi.org/10.1080/0142159X.2018.1430354 Ten Cate, T. J., Kusurkar, R. A., & Williams, G. C. (2011). How self-determination theory can assist our understanding of the teaching and learning processes in medical education. Medical Teacher, 33(12), 961–973. https://doi.org/10.3109/0142159X.2011.595435 Kusurkar, R. A., Croiset, G., Mann, K. V., Custers, E., & Ten Cate, O. (2012). Have motivation theories guided the development and reform of medical education curricula? A review of the literature. Academic Medicine, 87(6), 735–743. https://doi.org/10.1097/ACM.0b013e318253cc0e Evans, D. J., Zeun, P., & Stanier, R. A. (2014). Motivating student learning using a formative assessment journey. Journal of Anatomy, 224(3), 296–303. https://doi.org/10.1111/joa.12117 Sari, S. M., Inayati, I., & Sidiqa, A. (2021). Towards paradigm change of formative assessment in the undergraduate curriculum: The participatory action research (PAR). ICME Conference Book. https://doi.org/10.2991/assehr.k.210930.049 Pressentin, V. (2016). Towards tailored teaching: Using participatory action research to enhance the learning experience of Longitudinal Integrated Clerkship students in a South African rural district hospital. BMC Medical Education, 16, 82. Gibbs, G., & Simpson, C. (2005). Conditions under which assessment supports students’ learning. Learning and Teaching in Higher Education, 12, 3–31. Nagandla, K., Sulaiha, S., & Nalliah, S. (2018). Online formative assessments: Exploring their educational value. Journal of Advances in Medical Education & Professionalism, 6(2), 51–57. PMCID: PMC5856905 Marden, N. Y., Ulman, L. G., Wilson, F. S., & Velan, G. M. (2013). Online feedback assessments in physiology: Effects on students' learning experiences and outcomes. Advances in Physiology Education, 37(2), 192–200. https://doi.org/10.1152/advan.00092.2012 Creswell, J. W., & Creswell, D. J. (2018). Research design: Qualitative, quantitative, and mixed methods approaches (5th ed.). Thousand Oaks, CA: SAGE Publications. Rust, C., O’Donovan, B., & Price, M. (2005). A social constructivist assessment process model: How the research literature shows us this could be best practice. Assessment & Evaluation in Higher Education, 30(3), 231–240. Yardley, S., Teunissen, P. W., & Dornan, T. (2012). Experiential learning: AMEE guide No. 63. Medical Teacher. https://doi.org/10.3109/0142159X.2012.650741 Al-Kadri, H. M. A., Al-Moamary, M. S., & Magzoub, M. E., et al. (2011). Students’ perceptions of the impact of assessment on approaches to learning: A comparison between two medical schools with similar curricula. International Journal of Medical Education, 2, 44–52. Al-Kadri, H. M. A., Roberts, C., Al-Moamary, M. S., & Van der Vleuten, C. P. M. (2012). Exploring assessment factors contributing to students' study strategies: Literature review. Medical Teacher. https://doi.org/10.3109/0142159X.2012.656756 Mogali, S. R., Rotgans, J. I., Rosby, L., Ferenczi, M. A., & Low Beer, N. (2020). Summative and formative style anatomy practical examinations: Do they have impact on students' performance and drive for learning? Anatomical Sciences Education, 13(5), 581–590. https://doi.org/10.1002/ase.1931 Palmer, E., & Devitt, P. (2014). The assessment of a structured online formative assessment program: A randomized controlled trial. BMC Medical Education, 14, 8. https://doi.org/10.1186/1472-6920-14-8